Development and Formative Assessment of the Hearing Loss Toolkit for Self-Management - Arnold, Michelle L.; Oree, Preyanca; Sanchez, Victoria; Reed, Nicholas; Chisolm, Theresa (Seminars in Hearing, 2019)
Hearing aids are a demonstrated efficacious intervention for age-related hearing loss, and research suggests that good hearing loss self-management skills improve amplification satisfaction and outcomes. One way to foster self-management skills is through the provision of patient education materials. However, many of the available resources related to the management of hearing loss do not account for health literacy and are not suitable for use with adults from varying health literacy backgrounds. To address this issue, we developed the Hearing Loss Toolkit for Self-Management as part of a manualized, best practices hearing intervention used in large clinical trial. We incorporated health literacy recommendations from the U.S. Department of Health and Human Services, the Centers for Disease Control and Prevention, and the Agency for Healthcare Research and Quality in a series of modules that address a variety of common problem areas reported by adults with hearing loss. A formative assessment consisting of feedback questionnaires, semistructured interviews, and a focus group session with representatives from the target audience was conducted. Findings from the development assessment process demonstrate that the Hearing Loss Toolkit for Self-Management is suitable for use with adults with age-related hearing loss who have varying health literacy backgrounds and abilities.
Keywords: patient education; age-related hearing loss; health literacy; hearing aids